QUEST FOR UNLIMITED AUTONOMY: RESPONSIBLE FOR THE CURRENT CRISES IN THE CHURCH (Hekima Review, 2023)
This article agrees that there are serious crises facing the Church today, ranging from sexual abuse to calls for women’s ordination. Although the crises are not entirely new to the Church, there is a need to trace their root cause(s) to address them properly. This article argues that the quest for unlimited autonomy is responsible for the crises and suggests that recognition of legitimate diversity and respect for the common good are required to manage the crises.